Pelatihan Copywriting untuk Optimalisasi Pemasaran Digital Kepada SMK Bakti Nusantara 666 Kabupaten Bandung - Wazdi, Adi Indradi; Aisya Aprilia, Gadis (Ma'soem University, 2022)
One of the standard of a successful digital marketing campaign, is being able to maximize product and service promotion techniques using digital distribution channels such as; websites, Adwords, email or various other social network platforms. One of the ideal requirement of SMK graduates is able to succeed in the business world, therefore they must be equipped with good marketing skills. Seeing the importance of a marketer having Copywriting skills, Copywriting training is needed for them. The method used is the ABCD approach where the